Transmission of Helicobacter pylori: a role for food? - Duynhoven Yvonne T.H.P. van; Jonge Rob de (The World Health Organization, 2001)
Helicobacter pylori colonizes and grows in human gastric epithelial tissue and mucus. Its presence is associated with gastritis and there is substantial evidence that it causes peptic and duodenal ulcers and chronic gastritis. Since 1994, H. pylori has been classified as carcinogenic to humans. In industrialized countries, as many as 50% of adults are infected with the pathogen, while in the developing world, prevalence values of about 90% have been reported. As little is known about the mode of transmission, a literature search was carried out to determine whether food acts a reservoir or vehicle in the transmission of H. pylori. Although growth of the pathogen should be possible in the gastrointestinal tract of all warm-blooded animals, the human stomach is its only known reservoir. Under conditions where growth is not possible, H. pylori can enter a viable, but nonculturable state. H. pylori has been detected in such states in water, but not in food. Person-to-person contact is thought to be the most likely mode of transmission, and there is no direct evidence that food is involved in the transmission of H. pylori.